Eclectic-Procedural Innovation Management Approach with Regard to Community Management Within the German-Language Gaming Industry - Vindigni, Giovanni (Transactions on Engineering and Computing Sciences, 2023)
The gaming industry faces several challenges, such as inefficient development processes, shorter product lifecycles, dynamic knowledge, high staff turnover, and heterogeneous IT structures. To address these issues, this paper proposes an eclectic-procedural innovation management approach that integrates knowledge management methods and processes for the optimal cybernetic systematization of innovation management elements within the German-language gaming industry. Drawing on the human, organizational, and technological (HOT-Fit) model, this approach aims to enable gaming companies to analyze, assess, and optimize innovation management using agile and adaptive methods. The concept also involves modifications to the matrix organization and emphasizes the importance of open innovation, community management, and promoter functions. The eclectic approach offers several benefits, including greater efficiency in innovation processes, reduced risks, the exploitation of knowledge and innovation potential, and the preservation of innovation power. However, a shift in mindset is required to systematically implement this approach in a process-oriented manner, focusing on improving organizational skills and adapting to the changing landscape of the gaming industry.